Diagnostics and treatment of Helicobacter pylori infection in adults: Clinical guidelines of the Russian gastroenterological association - V. T. Ivashkin; I. V. Mayev; T. L. Lapina; A. A. Sheptulin; A. S. Trukhmanov; Ye. K. Baranskaya; R. A. Abdulkhakov; O. P. Alekseyeva; S. A. Alekseyenko; N. N. Dekhnich; R. S. Kozlov; I. L. Klyaritskaya; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of publication. To present indications for antihelicobacter therapy, methods and sequence of diagnostics and eradication treatment of Helicobacter pylori (H. pylori) infection to general practitioners. Key points. Chronic gastritis caused by H. pylori infection, including that in «asymptomatic» patients can be considered to be an indication for H. pylori eradication therapy both as etiological treatment and opportunistic screening diagnostics for gastric cancer prevention. Indications for obligatory antihelicobacter therapy include stomach and a duodenum peptic ulcer (PU), stomach MALT-lymphoma, early gastric cancer with endoscopic resection. Breath test with 13С-labeled urea, laboratory test for assessment of anti-H. pylori antibodies in feces, rapid urease test and serological method can be recommended for primary diagnostics of infection. Serological test is not applicable after antihelicobacter therapy. According to the bulk of regional studies clarithromycin resistance level of H. pylori strains in Russia does not exceed 15%. Obtained data indicate the absence of high metronidazole-resistance of H. pylori as well as double resistance to clarithromycin and metronidazole. Standard triple therapy including proton pump inhibitor (PPI), clarithromycin and amoxicillin is recommended as first-line treatment for H. pylori eradication. Standard triple therapy should be carried out, applying various means that increase its efficacy. Alternatively to standard triple therapy, first-line eradication treatment may include four-component bismuth tripotassium dicitratebased therapy or non-bismuth quadrotherapy which includes PPI, amoxicillin, clarithromycin and metronidazole. Quadrotherapy with bismuth tripotassium dicitrate can also be applied as a basic mode of the second line treatment at inefficiency of standard triple therapy. Alternative mode of second line eradication treatment includes PPI, levofloxacin and amoxicillin. Levofloxacinbased triple therapy prescription in the presence of strict indications should be limited to gastroenterologists. The third-line eradication treatment is adjusted individually according to the history of previous treatment modes. Eradication efficacy may be increased by prolongation of treatment up to 14 days, applicaiton of modern PPIs or increase of PPI doze, addition of bismuth tripotassium dicitrate or probiotic. Conclusion. In each case of H. pylori detection it is reasonable to consider eradication therapy that is especially actual as H. pylori infection eradication is recognized as effective method of stomach cancer prevention. H. pylori eradication optimization methods can be applied both to standard and alternative modes while combination of these approaches allows to achieve the best result in a given patient.